Heating of flint artifacts from the site of Boker Tachtit (Israel) was not detected using FTIR peak broadening. (April 2017) - Goder-Goldberger, Mae; Weiner, Steve; Barzilai, Omry; Boaretto, Elisabetta
Abstract: Heat treatment of flint changes its mechanical properties and improves its knappability. Here we examine flint artifacts from two occupational levels at the site of Boker Tachtit (Israel). Boker Tachtit is an important site for understanding the Middle to Upper Paleolithic transition in the Levant. The thin and stratified archeological levels together with a well-defined lithic technology make the site suitable for addressing the issue of heat treatment of raw materials for tool production. We use Fourier transform infrared spectroscopy to assess heat treatment of flint artifacts and compare them to geogenic flint nodules collected in Wadi Zin, < 20 m, from the site. We demonstrate that even though the broadening of the 512 and 467 cm − 1 peaks can be used to detect heating of these types of flint, we found no evidence that the archeological flint artifacts had been heated in such a way as to cause peak broadening. The observed potlids and cracking of flint, which are sometimes used to visually identify heating, do not generally correlate with peak broadening. Highlights: FTIR analytical methods show intentional heating is consistent with broadening of 512 cm - 1 and 467 cm - 1 peaks. Comparison between FTIR X/Y values of debitage and geological samples imply there was no intentional heating of artifacts. Experimental heating of flint show that at 400 °C there is a lowering of X/Y values as the result of peak broadening. Lowering of X/Y values also occurs when flint is heated for a long duration beneath sediment with max. temp. of 310 °C.